Is it a Social Need to Engage Young Mothers in Science? - Ergashevna, Azimova Ziyoda; Shakhobidinovna, Abdurakhmanova Sayyorakhan (International Journal on Integrated Education, 2023)
In this article discussed about is it a social need to engage young mothers in sciences and given some important information about this.